The Awareness of Indonesian Students Toward Autonomous Learning - Dony Marzuki (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
This writing reports the finding of a quantitative study which sought to find out the awareness of Indonesian  students toward autonomous  learning.  This was a survey to twelve Indonesian  students at their first year at Flinders  University. The survey used adapted and revised questionnaire  about autonomous  learning which was answered on-line by respondents. Survey Gizmo was utilized for this purpose. Analysis of the data by using SPSS ver. 15.0 showed that most Indonesian students from various different background  such as gender, age, hometown, occupation,  and  field of study have already aware of autonomous  learning  at almost the same level. Little different of autonomous  learning  level appeared  on the comparison  to hometowns of respondents.  Respondents from Java  had higher level of autonomous  learning than those from outside Java. Since this study involved small proportion of Indonesian  students in a specific place of Australia, similar study needs to be conducted with wider scope to find out the real condition.